Meaningless, Death, and Responsibilty: Existential Themes in Career Counselling - Koehn, Corinne V. (Canadian Journal of Counselling and Psychotherapy, 2011)
The position taken in this article is that existential thought is appropriate and applicable to career counselling. Three existential concerns, meaninglessness, death, and responsibility, are discussed and their applicability to career counselling is demonstrated. Career counselling exercises which help to introduce the client to these themes are identified. It is the belief of the author that career decision-making is enhanced, in some instances, by the client and counsellor engaging in an open and intimate examination of these existential motifs.